Intraoperative protective mechanical ventilation and risk of postoperative respiratory complications: hospital based registry study - Ladha, Karim (BMJ, 2015)
Objective To evaluate the effects of intraoperative protective ventilation on major postoperative respiratory complications and to define safe intraoperative mechanical ventilator settings that do not translate into an increased risk of postoperative respiratory complications. Design Hospital based registry study. Setting Academic tertiary care hospital and two affiliated community hospitals in Massachusetts, United States. Participants 69 265 consecutively enrolled patients over the age of 18 who underwent a non-cardiac surgical procedure between January 2007 and August 2014 and required general anesthesia with endotracheal intubation. Interventions Protective ventilation, defined as a median positive end expiratory pressure (PEEP) of 5 cmH(2)O or more, a median tidal volume of less than 10 mL/kg of predicted body weight, and a median plateau pressure of less than 30 cmH(2)O. Main outcome measure Composite outcome of major respiratory complications, including pulmonary edema, respiratory failure, pneumonia, and re-intubation. Results Of the 69 265 enrolled patients 34 800 (50.2%) received protective ventilation and 34 465 (49.8%) received non-protective ventilation intraoperatively. Protective ventilation was associated with a decreased risk of postoperative respiratory complications in multivariable regression (adjusted odds ratio 0.90, 95% confidence interval 0.82 to 0.98, P=0.013). The results were similar in the propensity score matched cohort (odds ratio 0.89, 95% confidence interval 0.83 to 0.97, P=0.004). A PEEP of 5 cmH(2)O and median plateau pressures of 16 cmH(2)O or less were associated with the lowest risk of postoperative respiratory complications. Conclusions Intraoperative protective ventilation was associated with a decreased risk of postoperative respiratory complications. A PEEP of 5 cmH(2)O and a plateau pressure of 16 cmH(2)O or less were identified as protective mechanical ventilator settings. These findings suggest that protective thresholds differ for intraoperative ventilation in patients with normal lungs compared with those used for patients with acute lung injury.